Analysis of Risk Factors for Perioperative Acute Kidney Injury and Management Strategies - Yu, Xiang; Feng, Zhe (Frontiers in Medicine, 2021)
Acute kidney injury (AKI) is a serious clinical syndrome, and one of the common comorbidities in the perioperative period. AKI can lead to complications in surgical patients and is receiving increasing attention in clinical workup. In recent years, the analysis of perioperative risk factors has become more in-depth and detailed. In this review, the definition, diagnosis, and pathophysiological characteristics of perioperative AKI are reviewed, and the main risk factors for perioperative AKI are analyzed, including advanced age, gender, certain underlying diseases, impaired clinical status such as preoperative creatinine levels, and drugs that may impair renal function such as nonsteroidal anti-inflammatory drugs (NASIDs), ACEI/ARB, and some antibiotics. Injectable contrast agents, some anesthetic drugs, specific surgical interventions, anemia, blood transfusions, hyperglycemia and malnutrition are also highlighted. We also propose potential preventive and curative measures, including the inclusion of renal risk confirmation in the preoperative assessment, minimization of intraoperative renal toxin exposure, intraoperative management and hemodynamic optimization, remote ischemic preadaptation, glycemic control and nutritional support. Among the management measures, we emphasize the need for careful perioperative clinical examination, timely detection and management of AKI complications, administration of dexmedetomidine for renal protection, and renal replacement therapy. We aim that this review can further increase clinicians' attention to perioperative AKI, early assessment and intervention to try to reduce the risk of AKI.